2012
DOI: 10.1103/physrevlett.109.187004
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Heavy Fermion Superconductivity in the Nonmagnetic Quadrupolar SystemPrTi2Al20

Abstract: We report the discovery of a pressure-induced heavy fermion superconductivity in a nonmagnetic orbital ordering state in the cubic compound PrTi(2)Al(20). In particular, we found that the transition temperature and the effective mass associated with the superconductivity are dramatically enhanced as the system approaches the putative quantum critical point of the orbital order. Our experiment indicates that the strong orbital fluctuations may provide a nonmagnetic glue for Cooper pairing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(166 citation statements)
references
References 30 publications
3
162
0
Order By: Relevance
“…The leading instability in the phase IV is determined by the smaller one of the two coefficients (19). Note that min{a u , a v } < a due to the linear term inQ as far asQ is not so large.…”
Section: Phase Boundariesmentioning
confidence: 97%
See 1 more Smart Citation
“…The leading instability in the phase IV is determined by the smaller one of the two coefficients (19). Note that min{a u , a v } < a due to the linear term inQ as far asQ is not so large.…”
Section: Phase Boundariesmentioning
confidence: 97%
“…Anisotropy in the orbital sector in these systems is manifested in the strong anisotropy of the critical field and the phase diagram strongly dependent on the field direction. 9,10,17,18) Superconductivity appears in a couple of compounds near the quadrupole ordered phases, 7,19) and it is expected that orbital fluctuations in the non-Kramers doublet in the Pr ions contribute to its realization.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies have revealed various interesting states in the cubic Γ 3 doublet systems, in particular in Pr-based intermetallic compounds [8][9][10][11][12]. However, Pr-based cubic Γ 3 doublet systems usually have well-localized quadrupole moments, and thus until quite recently there have been no study on the quadrupolar instability by tuning the c-f hybridization.PrT r 2 Al 20 (T r = Ti, V) has been reported as a rare example of cubic Γ 3 -doublet based Kondo lattice systems where one may tune the hybridization strength between quadrupole moments and conduction electrons by chemical substitution and by pressure [13,14]. These materials have the nonmagnetic Γ 3 CEF ground state with the well separated excited state at ∆ CEF ∼ 60 K (Ti) and 40 K (V), as confirmed by various experiments [13,15,16], and * Electronic address: satoru@issp.u-tokyo.ac.jp exhibit the respective ferro-and antiferro-quadrupole ordering at T Q = 2.0 K (Ti) and 0.6 K (V) [13,15,17].…”
mentioning
confidence: 99%
“…PrT r 2 Al 20 (T r = Ti, V) has been reported as a rare example of cubic Γ 3 -doublet based Kondo lattice systems where one may tune the hybridization strength between quadrupole moments and conduction electrons by chemical substitution and by pressure [13,14]. These materials have the nonmagnetic Γ 3 CEF ground state with the well separated excited state at ∆ CEF ∼ 60 K (Ti) and 40 K (V), as confirmed by various experiments [13,15,16], and * Electronic address: satoru@issp.u-tokyo.ac.jp exhibit the respective ferro-and antiferro-quadrupole ordering at T Q = 2.0 K (Ti) and 0.6 K (V) [13,15,17].…”
mentioning
confidence: 99%
“…For the Pr-skutterudites, PrFe 4 P 12 and PrOs 4 Sb 12 show heavy fermion behavior and the magnetic field induced phase transition due to the level-crossing [1]. Recently, the pressure enhanced superconducting transition temperature in the quadrupole ordered state in PrTi 2 Al 20 was reported [15]. With increasing pressure, T c is increased accompanying the mass enhancement.…”
Section: Resultsmentioning
confidence: 98%